A multifunctional Co-based metal–organic framework: heterogeneous catalysis, chemiluminescence sensing and moisture-dependent solvatochromism. Issue 35 (21st August 2018) - Xie, Ming-Hua; Wang, Ya; Li, Ruo-Fei; Dong, Peng-Yu; Hou, Gui-Hua; Shao, Rong; Xi, Xin-Guo; Guan, Rong-Feng; Yang, Xiu-Li
Abstract : A highly integrated metal–organic framework with multiple applications was studied both experimentally and theoretically. Abstract : Crystalline materials with multi-catalytic applications are of great value to both fundamental research and practical applications. The platform of metal–organic frameworks (MOFs) is utilized to fabricate a microporous versatile catalyst with high stability. Self-assembly of a flexible ligand, 4-(4-carboxybenzylamino)benzoic acid (H2 CBBA), with Co(ii ) resulted in a 3D framework, CBBA-Co, with Co3 O clusters exposed in the zigzag channels. Upon in situ activation, CBBA-Co exhibited multiple heterogeneous catalytic activities. Theoretical calculations were carried out to give insights into the catalytic process. In addition, CBBA-Co also showed promising potential in optical sensing by virtue of its catalytic activity. The luminol chemiluminescence was greatly enhanced by CBBA-Co, and linear determination of the concentration of H2 O2 in the range of 0–30% was established. The successful implementation of CBBA-Co indicates the feasibility and promising future of employing MOFs as an efficient platform for the fabrication and study of multifunctional catalysts, both experimentally and theoretically.